Realizing Good Governance through the Implementation of Electronic Procurement Services (LPSE) in Batam City - Debby Mayani Sirait; Lubna Salsabila; Timbul Dompak; Karol Teovani Lodan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
This study aims to explore the implementation of e-Procurement and the challenges faced, along with proposing effective solutions to overcome these obstacles concerning the implementation of Electronic Procurement Services (LPSE) in Batam City. By examining the practical aspects and identifying potential hindrances, this research contributes to the improvement of public service quality through the utilization of electronic procurement mechanisms. The provision of efficient and accurate public services is crucial for meeting the basic needs and civil rights of citizens, encompassing goods, services, and administrative assistance provided by public service providers. In the era of rapid information and globalization, it is essential to implement swift and precise public services to prevent social upheaval and potential national disintegration that could lead to division and harm to the nation and the state. The quality of public services often suffers due to a lack of transparency and accountability in their implementation. One of the government's endeavors to address this issue is the application of good governance principles, aiming to deliver excellent services to the community. E-Procurement, the procurement of goods and services through information technology and electronic transactions, has been introduced as a means to enhance efficiency and transparency in accordance with legal provisions. To facilitate this, an electronic unit responsible for goods and services procurement, known as the Electronic Goods and Services Procurement Service (LPSE), has been established within Ministries, Institutions, and Regional Authorities. This research adopts a sociological juridical approach, combining direct field observation with extensive literature research. Primary data is gathered through field observations and interviews conducted at the Batam City Government (PEMKO), while secondary data is obtained through comprehensive analysis of primary, secondary, and tertiary legal resources. The collected data is analyzed descriptively using qualitative analysis techniques.